Understanding the Impact of Chatbot Technology in Learning: Analysis of Utilization at SMA Negeri 5 Binjai - Mohammad Yusup; Arpan; Rezky Kurniawan (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to comprehend the impact of chatbot technology on learning, with a specific focus on analyzing its utilization at SMA Negeri 5 Binjai. Employing both qualitative and quantitative approaches, this study explores the implementation of chatbots in an educational context, including their applications in language learning, mental health support, and the teaching process. A comprehensive literature review was conducted to identify potential benefits and challenges associated with chatbot implementation in schools. The analysis results highlight the evolution of chatbot roles, ranging from basic functionalities to sophisticated capabilities in supporting the learning process. The research also encompasses a chatbot development model presented by Author and the findings from action research, providing practical insights into the use of chatbots in online learning media. Through surveys, interviews, and observations, research participants were engaged to provide a comprehensive perspective on the impact and acceptance of chatbot technology in the educational environment of SMA Negeri 5 Binjai. The outcomes of this research are anticipated to offer in-depth insights into how chatbots influence the learning process and lay the foundation for developing more effective strategies for chatbot utilization in educational institutions. The conclusions and recommendations from this study may assist policymakers, educators, and researchers in understanding the role of chatbots in enhancing the learning experience at SMA Negeri 5 Binjai and similar educational contexts.